ACTIVATION OF ADAPTOGENESIS AND BIORESOURCE POTENTIAL OF CALVES UNDER THE CONDITIONS OF TRADITIONAL AND ADAPTIVE TECHNOLOGIES - Semenov, V. G.; Baimukanov, D. A.; Kosyaev, N. I.; Alentayev, A. S.; Nikitin, D. A.; Aubakirov, A. A. (My University, 2019)
For the first time, the influence of the biological stimulators of the new generation, polystim and PV-1, on the growth and development of calves under the conditions of traditional growth technology and in premises of lighter type of the adaptive technology (individual houses and pavilions on the open area) and on the quality of young stock meat has been studied. The possibility of activating the adaptive processes and increasing the resistance of the organism of such animals under the influence of these biostimulators to low temperatures of the habitat for protein-carbohydrate-vitamin metabolism, the function of the hematopoietic organs and the buffer system is established. The tested preparations activated the growth and development of calves, reduced the incidence of respiratory organs and gastrointestinal tract. Впервые исследовано влияние биостимуляторов нового поколения Полистим и ПВ-1 на рост и развитие телят в условиях традиционной технологии выращивания и в помещениях более легкого типа адаптивной технологии (индивидуальные дома и павильоны на открытой площадке) и на качество мяса молодняка. Установлена возможность активирования адаптационных процессов и повышения устойчивости организма таких животных под действием этих биостимуляторов к низким температурам среды обитания для белково-углеводно-витаминного обмена, функции кроветворных органов и буферной системы. Испытанные препараты активировали рост и развитие телят, снизили поражение органов дыхания и желудочно-кишечного тракта.
BULLETIN OF THE NATIONAL ACADEMY OF SCIENCES OF THE REPUBLIC OF KAZAKHSTAN. - 2019
Keywords: импакт-фактор 2019; томсон; кларивате аналитикс; научный журнал; периодическое издание; отечественное издание; зарубежное авторы; выращивание телят; мясо молодняка; биостимуляторы